THE ROLE OF ISLAMIC BOARDING SCHOOLS IN BUILDING THE CHARACTER OF THE NATION - Ilpi Zukdi; Zulvia Trinova; Zulkifli Zulkifli; Ilman Nasution; Salmiwati Salmiwati (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Pesantren is the oldest educational institution in Indonesia.Pesantren is one of the traditional Islamic education systems in Indonesia which is also very influential in the social character of the Indonesian nation. Pesantren is an institution that always participates in building the nation's character in every condition with the characteristics of the pesantren itself.The problem in this study is how the role of pesantren in shaping the nation's morals and character. And the purpose of this study is to find out how the role of Islamic boarding schools in shaping the morals and character of the nation. This type of research is qualitative. The primary data used are books that discuss the curriculum and the role of Islamic boarding schools. While the secondary data used are books or research results that are directly related to the problem. The analytical method used is descriptive analysis, which is trying to explore the existing problems and then analyze them. The results of the study indicate that Islamic boarding schools have a role in shaping the morals and character of the nation. It is proven by the number of nations born from Islamic boarding schools. Islamic boarding schools need to be preserved and developed. That's how pesantren have many roles and provide concrete evidence in shaping the morals and character of the nation.